(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article covers in detail the socio - psychological foundations of reproductive function in families, the determination of the attitudes of young people towards age-old values such as marriage and family on the basis of scientific research, their psychological laying.